The integration of artificial intelligence in mathematics education: A systematic literature review - Wahyudi, Dwi Arisma; Prabawanto, Sufyani (Proceedings of International Conference on Research in Education, 2026)
The rapid advancement of technology in the Beta generation era continually presents new developments. To keep pace, the world of education must adapt accordingly. The alignment of technological progress with the utilization of artificial intelligence (AI) in education is expected to yield positive impacts. This research aims to analyze the utilization of AI technology implemented in mathematics learning. Employing a qualitative approach with a systematic literature review method, the study draws its literature from Google Scholar, focusing on publications from the last five years (2020 – 2025). The Publish or Perish application was used by the researchers to analyze and manage scientific references. The findings indicate that the utilization of AI can assist students in comprehending concepts and optimizing classroom learning.